THE INFLUENCE OF BRAND AWARENESS, BRAND IMAGE AND PERCEIVED QUALITY ON BRAND LOYALTY OPPO SMARTPHONE IN MADIUN - Tatik Mulyati; Aprilia B. Marheniput (Program Pascasarjana Universitas Gajayana, 2018)
One of the marketing success of businesses depend on company’s ability to continuously enhance their branding strategy in order to improve sales and keep customer loyal to the company’s products. The study aimed to analyze the relationship of brand awareness, brand image, and perceived quality on brand loyalty Oppo smartphone in Madiun. The data collection method using questionnaire ditributed to 114 respondents user Oppo smartphone in Madiun with judgement sampling technique. Data were analyzed using descriptive analysis, classification assumption test, and multiple linier regression analysis using SPSS 16.0. The independent variables used in this study are brand awareness, brand image, and perceived quality, while the dependen variable is brand loyalty. The result showed that brand awareness, brand image, and perceived quality was significant influenced with brand loyalty of Oppo smartphone in Madiun.